(untitled) (Bangladesh Journal of Nuclear Medicine, 2026)
Introduction: Thyroid carcinoma is one of the predominant endocrine malignancies. There are limited studies worldwide regarding the distribution of thyroid carcinoma in different areas of a country. Objective: The study was aimed at evaluating the distribution of thyroid carcinoma in different districts of Bangladesh. Materials and Methods: This was a retrospective observational study that included 100 thyroid carcinoma patients who came to INMAS, Dhaka, for radioiodine ablation after total thyroidectomy. The study period was from January 2022 to May 2022. Patients were selected according to the inclusion and exclusion criteria. Results: Out of a total of 100 patients, 72 patients were female and 28 patients were male. The age range was 15-63 years, with the mean age being 37 ± 8.4 years. There are a total of 8 divisions in Bangladesh: Dhaka, Chattogram, Barisal, Khulna, Rajshahi, Rangpur, Mymensingh, and Sylhet. Out of a total of 100 patients, Chattogram division had 42 patients, Dhaka division had 26 patients, Barisal division had 10 patients, Khulna division had 9 patients, Rajshahi division had 3 patients, Rangpur division had 3 patients, Mymensingh division had 5 patients, and Sylhet division had 2 patients. Out of a total of 42 patients in the Chattogram division, Brahmanbaria had 16 patients (the highest among all districts of Bangladesh); Comilla had 12 patients; Noakhali had 6 patients; Chadpur, Feni, and Lakshmipur each had 2 patients; and Chattogram & Cox’s Bazar each had 1 patient. Conclusion: Thyroid carcinoma was predominant in the Chattogram division, and among all districts of Bangladesh, Brahmanbaria was highest and next highest was the Comilla district. However, further large-scale and multicenter studies are needed to find out more specific distribution and Bangladesh J. Nuclear Med. 28(2): 293-297, July 2025